2019
DOI: 10.3390/ma12132198
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Beam Element Based on Quasi-3D Theory for Static Bending Analysis of Functionally Graded Beams

Abstract: In this paper, a 2-node beam element is developed based on Quasi-3D beam theory and mixed formulation for static bending of functionally graded (FG) beams. The transverse shear strains and stresses of the proposed beam element are parabolic distributions through the thickness of the beam and the transverse shear stresses on the top and bottom surfaces of the beam vanish. The proposed beam element is free of shear-looking without selective or reduced integration. The material properties of the functionally grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 45 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…at is the reason why numerous researchers focus on investigating the dynamic as well as static behaviors of the FGM structures, for example, beams [5][6][7][8][9][10], plates [11][12][13][14][15][16][17][18], shells [19][20][21], and other structures [22,23]. Many plate theories have been established and/or applied to investigate these structures, for example, classical plate theory (CPT), first-order shear deformation (FSDT), higherorder shear deformation theory (HSDT), and quasi-3D shear deformation theory.…”
Section: Introductionmentioning
confidence: 99%
“…at is the reason why numerous researchers focus on investigating the dynamic as well as static behaviors of the FGM structures, for example, beams [5][6][7][8][9][10], plates [11][12][13][14][15][16][17][18], shells [19][20][21], and other structures [22,23]. Many plate theories have been established and/or applied to investigate these structures, for example, classical plate theory (CPT), first-order shear deformation (FSDT), higherorder shear deformation theory (HSDT), and quasi-3D shear deformation theory.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades of the twentieth century, functionally graded materials (FGMs) have been become the most innovative composite materials and applied in many fields of engineering. [1][2][3][4][5] Because of their exotic properties, the application and investigation of FGM beams, plates and shells are increasing rapidly. Therefore, enormous beam, plate and shell theories were established and applied to scrutinize FGM structures, especially FGM plates.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the static bending of FG beams under different boundary conditions, Nguyen et al 55 developed an effective twonoded beam element with five DOFs per node based on Quasi-3D HSDT. Recently, Koutoati et al 56 used three finite element models based on CPT, FSDT and HSDT to study the static and free vibration behaviors of FGM sandwich beams. They concluded that the axial bending and shear coupling affect the behavior of the FGM sandwich beams in both statics and dynamics.…”
Section: Introductionmentioning
confidence: 99%